The Mekong regional health support project = (The World Bank in VietNam (WB), 2004)
The Mekong Regional Health Support Project for Vietnam aims to improve health services in the Mekong region and to enhance access to and coverage of these services, especially for the poor through: (i) strengthening the health financing policy framework and increasing the financial accessibility of health services for the poor and near-poor; (ii) improving the availability and quality of curative care, including responsiveness to changing disease patterns; (iii) increasing the capacity of preventive health activities; and (iv) building the capacity of the health workforce. The recent Quality Assurance Group (QAG) review of the project in July 2010 pointed out that the project development objective (PDO) and intermediate result indicators were not adequately formulated to measure the achievement of the project with reasonable validity and accuracy. The initial set of indicators was considered as lacking focus on outcomes, not specific on quality dimension to be measured, and vaguely formulated on patient satisfaction. Following the QAG review, the project team conducted a review mission to revisit the PDO and indicators. It was agreed with the government counterparts to revise the project results Indicators so as to better measure project achievements.